Motivation Moving Rubber Farmer Becomes Gold Miners Kenagarian Sikabau arbor Pulau Punjung Sub District Dharmasraya - Iman Rinaldi, Dante; Rianto, M.Pd, Slamet; Putri, S.Pd, M.Si, Rozana Eka (STKIP PGRI Sumbar, 2014)
ABSTRACTÂ This study aims to gain an overview of Motivation Rubber Farmers Turning Gold Miners Become views of: 1) internal motivation, 2) external motivation.This research is qualitative, the subject of this research through a snow ball, the data gathered through; 1) observation, 2) interviews, 3) documentation . Informants in this study is the village trustees, community leaders and community rubber farmers gold miners by 27 people. Testing the validity of the data in the study used data analysis techniques , data validity , and tringulasi. Based on the analysis of data and discussion of matters concluded as follows:1) internal motivation (from the inside) because the rubber farmers want to get better results than the previous revenue rubber farmers, in order to help the family economy. 2) Motivation external (outside) people Kenagarian Sikabau Dharmasraya District of Arbor Island, mostly motivated by peers, which is where gold miners who used rubber farmers interested to try, as seen from the income peers who get decent results from a gold minesr.